Operative and diagnostic hysteroscopy: A novel learning model combining new animal models and virtual reality simulation. (April 2017) - Bassil, Alfred; Rubod, Chrystèle; Borghesi, Yves; Kerbage, Yohan; Schreiber, Elie Servan; Azaïs, Henri; Garabedian, Charles
Abstract: Context: Hysteroscopy is one of the most common gynaecological procedure. Training for diagnostic and operative hysteroscopy can be achieved through numerous previously described models like animal models or virtual reality simulation. We present our novel combined model associating virtual reality and bovine uteruses and bladders. Study design: End year residents in obstetrics and gynaecology attended a full day workshop. The workshop was divided in theoretical courses from senior surgeons and hands-on training in operative hysteroscopy and virtual reality Essure ® procedures using the EssureSim™ and Pelvicsim™ simulators with multiple scenarios. Theoretical and operative knowledge was evaluated before and after the workshop and General Points Averages (GPAs) were calculated and compared using a Student's T test. Results: GPAs were significantly higher after the workshop was completed. The biggest difference was observed in operative knowledge (0, 28 GPA before workshop versus 0, 55 after workshop, p < 0, 05). All of the 25 residents having completed the workshop applauded the realism an efficiency of this type of training. The force feedback allowed by the cattle uteruses gives the residents the possibility to manage thickness of resection as in real time surgery. Furthermore, the two-horned bovine uteruses allowed to reproduce septa resection in conditions close to human surgery Conclusion: Teaching operative and diagnostic hysteroscopy is essential. Managing this training through a full day workshop using a combined animal model and virtual reality simulation is an efficient model not described before.